Alcohol to down-regulate negative and positive emotions: Extending our understanding of the functional role of alcohol in relation to posttraumatic stress disorder. (April 2021) - Weiss, Nicole H.; Goncharenko, Svetlana; Raudales, Alexa M.; Schick, Melissa R.; Contractor, Ateka A.
Highlights: PTSD was linked to alcohol misuse via down-regulation of negative/positive emotions. Extends current models by supporting a down-regulation function for positive emotions. PTSD-AUD interventions may target down-regulation of positive emotions. Abstract: Introduction: Functional models of posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD) underscore the role of internally-driven negative reinforcement. However, with the focus of these models being on negative emotions broadly, there is limited understanding of the effect of alcohol use to down-regulate specific forms of negative emotions or positive emotions generally. Among populations characterized by PTSD, there is growing evidence that positive emotions may elicit aversive reactions and thus be intentionally reduced, including via alcohol use. Objective: The current study examined the associations among PTSD symptom severity, alcohol use to down-regulate both negative (i.e., despondency and anger) and positive emotions, and alcohol misuse. Method: Data were collected from 320 trauma-exposed, substance-using individuals in the community ( M age = 35.78, 46.9% women). Results: Individuals with greater PTSD symptom severity reported significantly higher alcohol use to down-regulate despondency, anger, and positive emotions, which, in turn, were linked to greater alcohol misuse. Conclusions: Alcohol use may serve to down-regulate both negative (i.e., despondency and anger) and positive emotions, and these functions may help to explain the association of PTSD symptom severity to alcohol misuse. PTSD-AUD models may benefit from specifying a negatively reinforcing function of alcohol use in the context of positive emotions.